The Princess and Curdie - MacDonald, George, 1824-1905 (Puffin classics., 1994)
A miner's son is entrusted with the weighty task of saving the king, the princess, and consequently the kingdom. He is directed in his efforts by a mysterious fairy queen who provides monstrous but gentle creatures to aid him.